Influence of Knowledge Sharing and Employee Engagement on Job Satisfaction at a cosmetic company Central Java - Sekarlangit, Putri -; Utaminingtyas, Rara Ririn Budi; Rini, Nur - (Politeknik Negeri Semarang, 2024)
In the industrial competition, businesses must focus on elements that can raise employee satisfaction by fostering knowledge sharing and increasing employee involvement in the company in order to meet business objective. The aim of this study was to determine the impact of knowledge sharing and employee engagement on employees' job satisfaction at a cosmetics company in Central Java. This study used a questionnaire that has undergone validity and reliability testing to obtain data. Non-probability sampling with saturation sampling is the sampling approach employed in this study. All 40 employees of a cosmetics company in Central Java comprised the study's sample. The traditional assumption test, multiple linear regression analysis, the F test, the t test, and the coefficient of determination (R2) test are examples of data analysis techniques. The results of calculations using IBM SPSS version 25 software obtained the equation Y = 19.175 + 0.625x1 + 0.810x2+e, which indicates that the regression coefficient X1 is 0.625x1 in size. This demonstrates that raising X1 will result in an increase in Y of 0.625, and decreasing X1 will result in an increase in X2 of 0.810x2. This indicates that increasing the X2 variable will increase the Y variable by 0.810. Knowledge Sharing and Employee Engagement contributed 45.3%, although other factors that were not taken into account in this study had an impact on the remaining 54.7%.